SIFAT ELEKTROOPTIS SEBAGAI PARAMETER INDIKASI MUTU BERBAGAI JENIS MINYAK GORENG KEMASAN - Murni, Sri; Firdausi, K Sofjan; Hidayanto, Eko; Bawono P, Ari (BERKALA FISIKA, 2012)
Abstract In this paper, we introduce the change of polarization angleβ induced by external electric field, as a quality indication of several edible oils without preliminary treatment. The averagevalue ofβ in the interval of applied potential difference plays important role as level of number offree radicals produced in the edible oils. The samples used were olive oil, extra olive oil, palm oil,and corn oil. Theβ value was obtained by measurement of the change polarization angle as the function of magnitude the electric field on the samples. The electric field was produced by DCvoltage power supply on two parallel plates in a separated distance of 2.5 cm and in area of 5 cm× 3 cm. The source of light used was He-Ne laser 1 mW (λ=633 nm). The experiment result showsthat for all the fresh frying oil samples the polarization angle has value between 2.3× 10/V and3.3× 10-4 0/V in the experimental condition. The extra olive oil has the smallest value while palmoil has the greatest. According to the previous study, the olive oil is relatively the best oil.Keywords: frying oil, electrooptics, polarization angle